DIGITAL BUSPASS USING QR-CODE - Narmatha G.; Shri Warshini E.; Mrs. S. Kulandai Teresa (Galaxy International Interdisciplinary Research Journal, 2022)
Digital Bus Pass uses QR Code ”helps the user to get the bus through the internet instead of standing in long lines to get their pass. This program is useful for reducing our workload. Provides an effective database management solution. The passing generation of digital buses is useful for people who are having trouble with the current bus manufacturing strategy. This consists of two entries for one administrator and one for the user. The user needs to register by posting his / her information online. Thus, the user can easily access his or her information to log in. The bus driver can get his details about the passing of the bus by simply scanning their machine. This project has various pages and was developed with the help of ASP.Net as the main site and SQL SERVER as the background.